Open-cell bio-polyurethane foams based on bio-polyols from used cooking oil. (20th July 2022) - Polaczek, Krzysztof; Kurańska, Maria; Prociak, Aleksander
Abstract: Used cooking oil is a widely available and inexpensive waste with a high application potential as a feedstock for the bio-based polyurethane production. Usually, bio-polyols from vegetable oils have higher viscosity and lower hydroxyl values compared to commercial petrochemical polyols, which limits their usefulness. This article reports on the development of open-cell polyurethane foam systems wherein 100% of the polyol components were bio-polyols obtained from used cooking oil. What is particularly considered is the effect of bio-polyol properties (molecular weight, viscosity and hydroxyl value) on the properties of the final open-cell polyurethane systems - apparent density, thermal conductivity coefficient, content of closed cells, mechanical strength, brittleness and short-term water absorption. It was found that the key step in the synthesis of bio-polyols designed for open-cell polyurethane foams is the epoxidation reaction. The epoxy value has a significant effect on the occurrence of side reactions (mainly oligomerization) during the oxirane ring-opening process determining the properties of bio-polyols. The resulting open-cell foams were characterized by apparent densities from 12.4 to 13.3 kg/m 3, thermal conductivity coefficients from 36.6 to 38.2 mW/m∙K, and closed cell contents below 10%, which makes them comparable to commercial products. The results demonstrate that used cooking oil-based polyols can provide an alternative starting material for open-cell polyurethane foam production. Highlights: Used cooking oil was applied to obtain bio-polyols. The bio-polyols were produced using a solvent-free epoxidation and ring-opening process. A high epoxy value of epoxidized oil promoted oligomerization side reactions. 100% of the polyol component of the open-cell polyurethane foams was bio-polyol. The share of open cells in the foams of apparent densities <13 kg/m 3 was over 90%.